Epigenomic replication: linking epigenetics to DNA replication. - McNairn, A.J.; Gilbert, D.M. (BioEssays, 2003)
The information contained within the linear sequence of bases (the genome) must be faithfully replicated in each cell cycle, with a balance of constancy and variation taking place over the course of evolution. Recently, it has become clear that additional information important for genetic regulation is contained within the chromatin proteins associated with DNA (the epigenome). Epigenetic information also must be faithfully duplicated in each cell cycle, with a balance of constancy and variation taking place during the course of development to achieve differentiation while maintaining identity within cell lineages. Both the genome and the epigenome are synthesized at the replication fork, so the events occurring during S-phase provide a critical window of opportunity for eliciting change or maintaining existing genetic states. Cells discriminate between different states of chromatin through the activities of proteins that selectively modify the structure of chromatin. Several recent studies report the localization of certain chromatin modifying proteins to replication forks at specific times during S-phase. Since transcriptionally active and inactive chromosome domains generally replicate at different times during S-phase, this spatiotemporal regulation of chromatin assembly proteins may be an integral part of epigenetic inheritance.